Homeodomain leucine zipper protein controls the lobed leaf formation by modulating auxin distribution in watermelon - Yimei Zhou; Chuchu Chen; Shiqi Yi; Kejia Zhang; Xiaolong Lyu; Jinghua Yang; Zhongyuan Hu; Mingfang Zhang (Theoretical and Applied Genetics, 2025)

Application of galactinol to tomato enhances tolerance to cold and heat stresses - Yudong Liu; Li Zhang; Jian Ma; Sida Meng; Chunpeng Pang; Xiaomeng Zhao; Huidong Zhang; Shou Wang; Tao Xu; Yi He; Yufeng Liu; Mingfang Qi (Horticulture, Environment, and Biotechnology, 2022)

Silencing GhCOI1 in Gladiolus hybridus increases susceptibility to Alternaria brassicicola and impairs inducible defenses - Shanshan Seng; Chenyu Wu; Jian Wu; Xionghui Zhong; Junna He; Mingfang Yi (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Vegetation cover—another dominant factor in determining global water resources in forested regions - Xiaohua Wei; Qiang Li; Mingfang Zhang; Krysta Giles‐Hansen; Wenfei Liu; Houbao Fan; Yi Wang; Guoyi Zhou; Shilong Piao; Shirong Liu (Global Change Biology, 2018)
Forested catchments provide critically important water resources. Due to dramatic global forest change over the past decades, the importance of including forest or vegetation change in the assessment of water resources under climate change has been highly recognized by Intergovernmental Panel on Climate Change (IPCC); however, this importance has not yet been examined quantitatively across the globe. Here, we used four remote sensing‐based indices to represent changes in vegetation cover in forest‐dominated regions, and then applied them to widely used models: the Fuh model and the Choudhury‐Yang model to assess relative contributions of vegetation and climate change to annual runoff variations from 2000 to 2011 in forested landscape (forest coverage >30%) across the globe. Our simulations show that the global average variation in annual runoff due to change in vegetation cover is 30.7% ± 22.5% with the rest attributed to climate change. Large annual runoff variation in response to vegetation change is found in tropical and boreal forests due to greater forest losses. Our simulations also demonstrate both offsetting and additive effects of vegetation cover and climate in determining water resource change. We conclude that vegetation cover change must be included in any global models for assessing global water resource change under climate change in forest‐dominant areas.

Over-expression of LlHsfA2b, a lily heat shock transcription factor lacking trans-activation activity in yeast, can enhance tolerance to heat and oxidative stress in transgenic Arabidopsis seedlings - Haibo Xin; Hua Zhang; Xionghui Zhong; Qinglong Lian; Aixiang Dong; Li Cao; Mingfang Yi; Richen Cong (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Characterization and Functional Analysis of Transcription Factor LoMYB80 Related to Anther Development in Lily (Lilium Oriental Hybrids) - Juanjuan Sui; Junna He; Jian Wu; Benhe Gong; Xing Cao; Shanshan Seng; Ze Wu; Chenyu Wu; Chen Liu; Mingfang Yi (Journal of Plant Growth Regulation, 2015)

The NPR1 homolog GhNPR1 plays an important role in the defense response of Gladiolus hybridus - Xionghui Zhong; Lin Xi; Qinglong Lian; Xian Luo; Ze Wu; Shanshan Seng; Xue Yuan; Mingfang Yi (Plant Cell Reports, 2015)

Somatic embryogenesis and Agrobacterium-mediated transformation of Gladiolus hybridus cv. ‘Advance Red’ - Jian Wu; Chen Liu; Shanshan Seng; Muhammad Ali Khan; Juanjuan Sui; Benhe Gong; Chao Liu; Chenyu Wu; Xionghui Zhong; Junna He; Mingfang Yi (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

LlHSFA1, a novel heat stress transcription factor in lily (Lilium longiflorum), can interact with LlHSFA2 and enhance the thermotolerance of transgenic Arabidopsis thaliana - Benhe Gong; Jin Yi; Jian Wu; Juanjuan Sui; Muhammad Ali Khan; Ze Wu; Xionghui Zhong; Shanshan Seng; Junna He; Mingfang Yi (Plant Cell Reports, 2014)

Virus-induced gene silencing for comparative functional studies in Gladiolus hybridus - Xionghui Zhong; Xue Yuan; Ze Wu; Muhammad Ali Khan; Jin Chen; Xiaoxin Li; Benhe Gong; Yang Zhao; Jian Wu; Chenyu Wu; Mingfang Yi (Plant Cell Reports, 2014)

Involvement of Ca2+ and CaM3 in Regulation of Thermotolerance in Lily (Lilium longiflorum) - Xing Cao; Jin Yi; Ze Wu; Xian Luo; Xionghui Zhong; Jian Wu; Muhammad Ali Khan; Yang Zhao; Mingfang Yi (Plant Molecular Biology Reporter, 2013)

MRI can reveal metabolic changes in lily bulbs in vivo during dormancy release - HaoJun Han; MingFang Yi (Science China Life Sciences, 2012)

Cloning and characterization of HsfA2 from Lily (Lilium longiflorum) - Haibo Xin; Hua Zhang; Li Chen; Xiaoxin Li; Qinglong Lian; Xue Yuan; Xiaoyan Hu; Li Cao; Xiuli He; Mingfang Yi (Plant Cell Reports, 2010)